The Chewable Tablet of Guava Leaves Extract (Psidium guajava L.) with Breadfruit Starch as Binder - Lestari, Pramulani Mulya; Pamungkas, Septiana Tri (Jurnal Jamu Indonesia, 2019)
Breadfruit starch can be used as a binder on the chewable tablet because it consists of amylose and amylopectin which can increase the cohesiveness and make a good bond with the powder. Guava leaves extract can kill the bacterial growth of Streptococcus mutans so it can be served to prevent dental caries. This research aimed to know whether increased concentrations of breadfruit starch can affect the physical characteristics of the chewable tablet of guava leaves extract. The chewable tablets were formulated into 4 formulas with different concentration of mucilago breadfruit starch, such as 10%, 13%, 16% and 19%. Breadfruit starch as a binder obtained from an almost ripe the breadfruit and then was crushed and soaked to occur separation between water immersion and amylum, and then amylum was dried and made as mucilago and the mucilago was added into the formula. The result of the characteristic of starch, the powder was true breadfruit starch. The flowability and particle size distribution of granule was evaluated. Then, the granule was made into the chewable tablet. The research result showed that the increase of mucilago breadfruit starch concentration increased the hardness and decreased friability of chewable tablet.